2022
DOI: 10.1111/jocs.16408
|View full text |Cite
|
Sign up to set email alerts
|

Transapical‐transcatheter aortic valve implantation in patients without transvascular options: Modified transapical approach

Abstract: Objectives: Outcomes in patients with iliofemoral and concomitant iliofemoralremote arteriopathies who cannot undergo transfemoral or other alternative transvascular approaches have not been studied so far. This study aimed to evaluate the early and midterm outcomes after transapical (TA)-transcatheter aortic valve implantation (TAVI) in patients with femoral and femoral-remote arteriopathies who cannot undergo transvascular approaches.Methods: Multimorbid patients with severe aortic stenosis and distinct pana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Some studies have suggested that TA-TAVR is associated with poor outcomes compared with SAVR. 4,5 In this context, this report by Useini et al 6 in this issue of the Journal is timely and relevant. The authors present data regarding 72 consecutive patients who underwent aortic valve replacement using a modified artery-no-touch TA transcatheter aortic valve implantation (TAVI).…”
mentioning
confidence: 88%
“…Some studies have suggested that TA-TAVR is associated with poor outcomes compared with SAVR. 4,5 In this context, this report by Useini et al 6 in this issue of the Journal is timely and relevant. The authors present data regarding 72 consecutive patients who underwent aortic valve replacement using a modified artery-no-touch TA transcatheter aortic valve implantation (TAVI).…”
mentioning
confidence: 88%